A Systematic Literature Review on the Interrelation of Human Resource Practices, Corporate Social Responsibility, and Financial Performance in Emerging Markets - Maziah Azzahroh; Suci Arimbi; Tarissa Denia; Yossie Rossanty (Journal Social Society, 2025)
The growing complexity of business operations in emerging markets highlights the urgency of understanding how Human Resource Practices (HRPs) and Corporate Social Responsibility (CSR) jointly influence Financial Performance (FP). Although prior studies have examined these constructs separately, a comprehensive review that integrates their interrelationships remains scarce, particularly in institutionally diverse and volatile environments. This study aims to systematically review and synthesize existing evidence on the HRP–CSR–FP nexus to clarify its theoretical and practical significance. Using a Systematic Literature Review (SLR) approach, 62 peer-reviewed journal articles published between 2000 and 2024 were selected based on predefined criteria, including relevance to the topic, methodological rigor, and focus on emerging market contexts. Data were analyzed using PRISMA guidelines and thematic synthesis. The findings indicate that the strategic alignment of HRPs and CSR initiatives enhances FP through mechanisms such as employee engagement, organizational legitimacy, and stakeholder trust. Moreover, contextual factors such as national culture, regulatory quality, and institutional voids moderate these relationships, underscoring the importance of localized strategies. The synthesis concludes that while theoretical perspectives such as the Resource-Based View, Stakeholder Theory, and Social Exchange Theory provide explanatory strength, gaps remain in addressing causal mechanisms and multi-level dynamics. This review contributes by integrating fragmented insights into a unified conceptual framework, highlighting research gaps, and offering practical guidance for managers in emerging markets. Future studies are encouraged to employ longitudinal, comparative, and multi-level designs to capture deeper causal and contextual variations